The Effect of Eudaimonic Well-being, Hedonic Well-being, and High Performance Work System on Job Performance in the Manufacturing Industry with Affective Commitment as Mediation - Adi Neka Fatyandri; Zidane Huang (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to see how eudaimonic well-being, hedonic well-being, and high-performance work systems affect job performance with the mediating effect of affective commitment. This study used cross-sectional data and a quantitative approach. Sampling was carried out by distributing questionnaires to employees of electronic manufacturing companies in Batam City. Then test the hypothesis using the SPSS application. The results showed that eudaimonic well-being and hedonic well-being did not affect job performance, but high-performance work systems (HPWS) and affective commitment affected job performance. In addition, it was found that there was an influence of eudaimonic well-being and HPWS on affective commitment but hedonic well-being did not affect affective commitment. Then the affective commitment variable does not have a mediating role between eudaimonic well-being, hedonic well-being, and job performance, but affective commitment has a mediating role between HPWS and job performance. Companies can make this research as an assessment and discuss research findings and how to apply them in improving work performance. The company is expected to engage relevant stakeholders in discussing how research findings can be integrated into the company's strategy and policies.